Safety of Living Donation of Hematopoietic Stem Cells. Issue 6 (June 2016) - Szer, Jeff; Elmoazzen, Heidi; Fechter, Mirjam; Hwang, William; Korhonen, Matti; Miller, John; Mengling, Thilo; Shaw, Bronwen; Stein, Jerry
Abstract : Abstract: More than 12 000 volunteer unrelated hematopoietic stem cell donations are undertaken annually, and the World Marrow Donor Association established an expert committee to examine all reports of adverse events affecting donors globally, eventually making such reporting a necessary part of World Marrow Donor Association accreditation. The committee evaluates and responds to reported events in a nonpunitive confidential process designed to alert the community of rare events which might be missed by local follow-up. Each report is evaluated by the committee for imputability (causal link between the donation and the adverse event) and compared with that submitted by the reporting registry. In 2014, there were 50 reports received from 16 different registries in 15 countries. There were 16 reports of malignancies arising in donors including 3 hematologic malignancies. All but 2 of the 16 occurred more than a year after donation. There were 4 reports of autoimmune phenomena in donors all occurring more than a year postdonation. Of the 30 remaining events, 6 were allergic, 4 cardiac, 3 gastrointestinal, 2 infections, 2 pulmonary, and 13 miscellaneous. Causation was assessed differently to the reporting registry in 17 events with 6 thought to be less likely causally linked to the donation and 10 more likely with 1 requiring more information. Volunteer unrelated hematopoietic stem cell donation is a safe and effective altruistic contribution to the treatment of patients with life-threatening hematologic disorders. A decade of detailed examination of adverse donor events has contributed to the safety of these donations. Abstract : The World Marrow Donor Association examines adverse events affecting volunteer unrelated hematopoietic stem cell donors globally and reports that stem cell donation is a safe and effective altruistic contribution to the treatment of patients with life-threatening hematologic disorders.